Organic synthesis via examination of selected natural products - Hart, David J. (World Scientific Pub., 2011)
Complete with problems and solutions, this book is written for advanced graduate and undergraduate students to expose them to a variety of strategies for the synthesis of organic compounds. This is done largely within the context of natural products synthesis, but includes some unnatural products synthesis. Multiple approaches to each group of synthesis targets are presented, and the approaches are compared with one another with an eye on similarities and differences. General problems in organic synthesis (for example, strategies for the preparation of 6-membered rings and 5-membered rings, th.